2019
DOI: 10.2478/jomb-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers for Prediction of Hypertensive Disorders of Pregnancy

Abstract: SummaryBackground:Gestational hypertension (GH) and pre eclampsia (PE) are the most common gestational complications. Several placental biochemical markers are used to predict GH/PE, but with conflicting results.Methods:The study aim was to estimate the biochemical markers’ ability to predict hypertensive disorders in pregnancy. On the first ultrasonographic examination, 104 healthy pregnant women were recruited. At the regular pregnancy check-ups, BMI, blood pressure, occurrence of gestational hypertension (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…The most plausible explanations of the pathogenesis of preeclampsia focus on the placenta (7). The initial event of placentation involves the formation of the non-invasive trophoblastic shell, which progresses into an invasive phenotype, causing an exponential rise in the entry of oxygenated maternal blood into the intervillous space (11). The opening of intervillous space and the consequent increase in PO 2 , reduces HIF-1 alpha expression, augmenting trophoblastic differentiation along the invasive pathway (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most plausible explanations of the pathogenesis of preeclampsia focus on the placenta (7). The initial event of placentation involves the formation of the non-invasive trophoblastic shell, which progresses into an invasive phenotype, causing an exponential rise in the entry of oxygenated maternal blood into the intervillous space (11). The opening of intervillous space and the consequent increase in PO 2 , reduces HIF-1 alpha expression, augmenting trophoblastic differentiation along the invasive pathway (11).…”
Section: Discussionmentioning
confidence: 99%
“…The initial event of placentation involves the formation of the non-invasive trophoblastic shell, which progresses into an invasive phenotype, causing an exponential rise in the entry of oxygenated maternal blood into the intervillous space (11). The opening of intervillous space and the consequent increase in PO 2 , reduces HIF-1 alpha expression, augmenting trophoblastic differentiation along the invasive pathway (11). Preeclampsia progresses through a proposed twostage model that includes poorly perfused placentation (Stage 1) arresting trophoblastic invasion, increasing vascular resistance and subsequent nutrient deprivation which modifies maternal metabolism to increase nutrient availability; inability to tolerate this modification leads to the clinical manifestations of preeclampsia (Stage 2) (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypoglycemic power of Se and its ability to delay diabetes complications are thus exalted during type II diabetes, but exclusively in deficient or sub-deficient people in this micronutrient (22). However, a French study reported that the anti-diabetogenic properties of Se occur only in men and reduce the risk that they develop type II diabetes to 50% (23). The beneficial effect of this micronutrient supplementation (200 mg/d for 06 weeks) in the reduction of exacerbated state of insulin resistance has been proven in other diseases such as polycystic ovary syndrome (24) and central obesity (25).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of this micronutrient supplementation (200 mg/d for 06 weeks) in the reduction of exacerbated state of insulin resistance has been proven in other diseases such as polycystic ovary syndrome (24) and central obesity (25). In contrast, other studies have advised against the use of Se supplementation, considering it as a promoting factor of type II diabetes in healthy women (23) and mice (8), which leads to the worsening of sugar metabolism disorders (24), especially in the Caucasian race (12), and in seleniferous zones (9). Se is a trace element involved in the regulation of energy metabolism at several levels (11).…”
Section: Discussionmentioning
confidence: 99%